The Effect of Profitability and Environmental, Social, Governance Disclosure on Company Value (Case Study on Basic Materials Sub-Sector Companies Listed on the Indonesia Stock Exchange in 2021-2024) - Adi Mulyadi; Khairunnisa (Dinasti Publisher, 2025)
This study aims to examine the effect of profitability and disclosure of Environmental, Social, and Governance (ESG) aspects on company value in basic materials sub-sector companies listed on the Indonesia Stock Exchange during the period 2021-2024. The data used are financial reports, sustainability reports, and ESG disclosure scores measured based on GRI standards. The method applied is panel data regression to test the relationship simultaneously and partially. The results of the study show that profitability has a positive impact on company value, as well as the disclosure of ESG aspects as a whole which has been proven to have a significant effect on company value. These findings confirm that financial performance and company sustainability efforts are key factors in increasing company value and attracting investor interest. Therefore, companies in the basic materials sector are advised to increase their level of transparency and sustainability performance in order to create optimal long-term value.